2022
DOI: 10.1111/resp.14309
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of influenza and pneumococcal vaccines on chronic obstructive pulmonary disease exacerbations

Abstract: Background and objective Single‐study evidence of separate and combined effectiveness of influenza and pneumococcal vaccination in patients with chronic obstructive pulmonary disease (COPD) is limited. To fill this gap, we studied the effectiveness of trivalent seasonal influenza vaccine (TIV) and 23‐valent pneumococcal polysaccharide vaccine (PPSV23), separately and together, at preventing adverse COPD outcomes. Methods Our study used a self‐controlled, before‐and‐after cohort design to assess the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Chronic airway disease seriously affects the quality of life of patients, and its high incidence rate, high disability rate, and high mortality bring heavy financial burden to patients and their families and society [ 7 ]. This study showed that the ratios of acute attacks, hospitalization times, treatment costs, and hospitalization times of patients with chronic airway disease who received the influenza vaccine were lower than those before vaccination, which is consistent with the results of other studies [ 10 , 16 , 17 ], which indicates that the influenza vaccination can prevent the acute attacks of chronic airway disease. Respiratory diseases are usually avoidable, and the cost of prevention is only a small part of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic airway disease seriously affects the quality of life of patients, and its high incidence rate, high disability rate, and high mortality bring heavy financial burden to patients and their families and society [ 7 ]. This study showed that the ratios of acute attacks, hospitalization times, treatment costs, and hospitalization times of patients with chronic airway disease who received the influenza vaccine were lower than those before vaccination, which is consistent with the results of other studies [ 10 , 16 , 17 ], which indicates that the influenza vaccination can prevent the acute attacks of chronic airway disease. Respiratory diseases are usually avoidable, and the cost of prevention is only a small part of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The estimates of effect by Li et al 1 for the efficacy of PSV‐23 are not that much larger than suggested by meta‐analyses of randomized controlled trials and a similar recent observational study in Hungary 2 . Walters et al 3 in the last Cochrane analysis of pneumococcal vaccines in COPD found a 41% reduction in pneumonia and a 40% reduction in exacerbations for PSV‐23, but no difference in hospitalizations or death.…”
mentioning
confidence: 85%
“…In a recent publication in Respirology , Li et al 1 present data from a 1‐year observational study of the impact of 23‐valent pneumococcal vaccine and influenza vaccine on hospitalizations in patients with COPD in Hebei province in China. In an attempt to adjust for seasonal variation in pathogens, they recorded exacerbations in the 3 years prior to vaccination and compared them in the 1 year following.…”
mentioning
confidence: 99%
See 2 more Smart Citations